EXAMINING PEER FACTOR IN THE DEVELOPMENT OF SOCIAL SKILLS OF MENTALLY DISABLED INDIVIDUALS IN REFERENCE TO THE TEACHERS’ VIEWS - Adanır, Sinan; Sen, Burcu Gezer (My University, 2021)
The aim of this study is to identify the teachers' views on the peer factor in the development of social skills of mentally disabled individuals. The research was conducted via phenomenology research design, a qualitative method. The participants of the research were composed of 30 teachers from the province of Bingol and its district Genc. They were selected using convenience sampling of purposive sampling method. The data were collected using a semi structured interview developed by the researchers based on the views of experts. The data were analyzed using content analysis and descriptive statistics. The results revealed that majority of the participating teachers were of the opinion that mentally disabled individuals were positively affected by the peer factor when they started and sustained a relationship, expressed their feelings, dealt with the aggression and stress, solving problems and planning whereas a small group was not affected by the peer factor at all.
Keywords: Eğitim; Özel